Kiowa Belief and Ritual - Kracht, Benjamin R., 1955- (Book collections on Project MUSE., 2017)
"Brings together materials gleaned from the Laboratory of Anthropology (Santa Fe) fieldnotes, augmented by Alice Marriott's fieldnotes, to significantly enhance the existing literature concerning Plains Indians religions."--Provided by publisher.